Venous thoracic outlet syndrome and hemodialysis - Davies, Mark G.; Hart, Joseph P. (Frontiers in Surgery, 2023)
Venous Thoracic Outlet syndrome in hemodialysis (hdTOS) is reported in 7-40% of patients needing a central venous catheter for dialysis and in 19-41% of hemodialysis patients who have had a prior central venous catheter. Half of these patients will be asymptomatic. The extrinsic mechanical compression of the subclavian vein at the costoclavicular triangle between the clavicle and 1st rib results in an area of external compression with a predisposition to intrinsic mural disease in the vein. The enhanced flow induced by the presence of a distal arteriovenous access in all patients and the presence of or a history of a central venous catheter in many patients exacerbates the subclavian vein’s response to ongoing extrinsic and intrinsic injury. Repeated endovascular interventions during the maintenance of vascular access accelerates chronic untreatable occlusion of the subclavian vein in the long term. Patients with hdTOS can present immediately after access formation with ipsilateral edema or longitudinally with episodes of access dysfunction. hdTOS can be treated in an escalating manner with arteriovenous access flow reduction to <1500ml/min, endovascular management, surgical decompression by first rib resection in healthy patients and medial clavicle resection in less healthy patients followed by secondary venous interventions, or finally, a venous bypass. hdTOS represents a complex and evolving therapeutic conundrum for the dialysis community, and additional clinical investigations to establish robust algorithms are required.